Respuesta :
Answer: X²+2x
Step-by-step explanation:
Use FOIL method
- First
- Inner
- Outer
- Last
Solve:
x(x+2)
=x²+2x
☽------------❀-------------☾
Hi there!
~
What is [tex]x(x+2)[/tex] expanded?
[tex]x(x+2)[/tex] in expanded form is :
[tex]x^2 + 2x[/tex]
Explanation :
Apply the distributive law: [tex]a( b + c ) = ab + ac[/tex]
[tex]x(x+2) = xx + x \times 2[/tex]
[tex]= xx + x \times 2[/tex]
Then you simplify : [tex]xx + x \times 2 : x^2 + 2x[/tex]
[tex]= x^2 + 2x[/tex]
❀Hope this helped you!❀
☽------------❀-------------☾